2016
DOI: 10.1182/blood.v128.22.5254.5254
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DDIT4 Is Correlated with NOTCH1 and High Molecular Risk in Acute Myeloid Leukemias

Abstract: In a meta-analysis, our team identified previously that DDIT4 expression is related with a worse outcome of several cancer types, including acute myeloid leukemia (AML). DDIT4 gene product is a repressor of mTOR activity and recent findings in the triple negative breast cancer model suggest that mTOR pathway inhibition lead to the enrichment of cancer stem cells, explaining indirectly the relationship between DDIT4 and the outcome and suggesting that a high DDIT4 expression could be related with expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pinto et al observed a significant positive correlation between DDIT4 and NOTCH1 expression, and both of them tend to highly express in high-risk AML patients. 24 These results indicate that DDIT4 expression may explain some of the aggressive features of AML by involving in the above pathways, though the exact role of DDIT4 in leukaemogenesis requires further study.…”
Section: Chemotherapy-only Groupmentioning
confidence: 82%
See 1 more Smart Citation
“…Pinto et al observed a significant positive correlation between DDIT4 and NOTCH1 expression, and both of them tend to highly express in high-risk AML patients. 24 These results indicate that DDIT4 expression may explain some of the aggressive features of AML by involving in the above pathways, though the exact role of DDIT4 in leukaemogenesis requires further study.…”
Section: Chemotherapy-only Groupmentioning
confidence: 82%
“…GO analysis demonstrated that genes ( WNT9A , NOTCH3 , SOCS1 , MCL1 , HIF1A , ALOX5 , CD47 , CXCR4 , CDK9 , HRAS , PLK3 , ETS2 and RPL5 ) involved in “acute and chronic myeloid leukaemia,” “bladder cancer,” “hedgehog signalling pathway,” “endometrial cancer” and “basal cell carcinoma” signalling pathways were significantly correlated with the DDIT4 expression. Pinto et al observed a significant positive correlation between DDIT4 and NOTCH1 expression, and both of them tend to highly express in high‐risk AML patients . These results indicate that DDIT4 expression may explain some of the aggressive features of AML by involving in the above pathways, though the exact role of DDIT4 in leukaemogenesis requires further study.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, reviewing the literature led to selecting genes of DDIT4, SULF1, miR-181d-5p and miR-148b-3p that are involved in CSCs amongst the key genes and hub miRNAs for our experimental validation [ 68 – 71 ]. Also, TPTEP1 was selected on topmost of the predicted lncRNAs for our experimental study that has target and interaction sites in untranslated region (UTR) and coding sequence (CDS) region for DDIT4 and SULF1, respectively, as found by prediction algorithms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in line with the study on gastric cancer displaying up-regulation of DDIT4 expression in the tumor tissues compared to the adjacent normal tissues as found by RT-qPCR and immunohistochemically staining [ 79 ]. Since earlier findings reported that inhibition of mTOR pathway is leading to enrichment of cancer stem cells, high DDIT4 expression could be related to expression of stem-cells markers [ 68 , 81 ]. As expected, up-regulation of DDIT4 expression was observed in colorectal CSC-enriched spheroids compared to HT-29 cancer cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that LGALS1 is a valuable drug target for KMT2A-r ALL (Juszczynski et al, 2010;Paz et al, 2018). Up-regulation of DDIT4 is associated with poor prognosis of AML (Cheng et al, 2020;Pinto et al, 2016Pinto et al, , 2017. CTGF/CCN2 encodes a connective tissue growth factor and is highly expressed in several pediatric and adult ALL and is associated with poor clinical outcome (Boag et al, 2007;Sala-Torra et al, 2007).…”
Section: Discussionmentioning
confidence: 99%